Down Modulation of Host Immune Response by Amino Acid Repeats Present in a Trypanosoma cruzi Ribosomal Antigen - Toro Acevedo, Carlos A.; Valente, Bruna M.; Burle-Caldas, Gabriela A.; Galvão-Filho, Bruno; Santiago, Helton da C.; Esteves Arantes, Rosa M.; Junqueira, Caroline; Gazzinelli, Ricardo T.; Roffê, Ester; Teixeira, Santuza M. R. (Frontiers in Microbiology, 2017)
Several antigens from Trypanosoma cruzi, the causative agent of Chagas disease, contain amino acid repeats identified as targets of the host immune response. Ribosomal proteins containing an Ala, Lys, Pro-rich repeat domain are among the T. cruzi antigens that are strongly recognized by antibodies from Chagas disease patients. Here we investigated the role of amino acid repeats present in the T. cruzi ribosomal protein L7a, by immunizing mice with recombinant versions of the full-length protein (TcRpL7a), as well as with truncated versions containing only the repetitive (TcRpL7aRep) or the non-repetitive domains (TcRpL7aΔRep). Mice immunized with full-length TcRpL7a produced high levels of IgG antibodies against the complete protein as well as against the repeat domain, whereas mice immunized with TcRpL7aΔRep or TcRpL7aRep produced very low levels or did not produce IgG antibodies against this antigen. Also in contrast to mice immunized with the full-length TcRpL7a, which produced high levels of IFN-γ, only low levels of IFN-γ or no IFN- were detected in cultures of splenocytes derived from mice immunized with truncated versions of the protein. After challenging with trypomastigotes, mice immunized with the TcRpL7a were partially protected against the infection whereas immunization with TcRpL7aΔRep did not alter parasitemia levels compared to controls. Strikingly, mice immunized with TcRpL7aRep displayed an exacerbated parasitemia compared to the other groups and 100% mortality after infection. Analyses of antibody production in mice that were immunized with TcRpL7aRep prior to infection showed a reduced humoral response to parasite antigens as well as against an heterologous antigen. In vitro proliferation assays with mice splenocytes incubated with different mitogens in the presence of TcRpL7aRep resulted in a drastic inhibition of B cell proliferation and antibody production. Taken together, these results indicate that the repeat domain of TcRpL7a acts as an immunosuppressive factor that down regulates the host B-cell response against parasite antigens favoring parasite survival in the mammalian host.